Penerapan Model Pembelajaran Audio-Visual Berbasis Digital untuk Meningkatkan Kemampuan Menyimak Teks Berita di SMP Negeri 1 Afulu - Zalukhu, Cisrad Anda Nita; Ndruru, Mastawati; Waruwu, Lestari; Bawamenewi, Arozatulo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study was motivated by the low listening skills of students. The purpose of this study was to improve students' listening skills through the application of a digital-based audio-visual learning model. The research method used was Classroom Action Research (CAR), which was conducted in two cycles. The research subjects were 26 seventh-grade students at SMP Negeri 1 Afufu in the 2024/2025 academic year, consisting of 16 male students and 10 female students. Research data were collected through questionnaires, observations, and written tests, then analyzed using qualitative and quantitative descriptive techniques by comparing learning outcomes in cycle I and cycle II. The results of the study show an increase in students' listening skills. The percentage of learning completeness increased from 65.21% in cycle I to 95% in cycle II. The percentage of learning effectiveness also increased from 69.87% in cycle I to 85.26% in cycle II. Thus, it can be concluded that the application of a digital-based audio-visual learning model is effective in improving students' listening skills, especially in learning news texts.